2000
DOI: 10.1038/sj.mp.4000681
|View full text |Cite
|
Sign up to set email alerts
|

A human myo-inositol monophosphatase gene (IMPA2) localized in a putative susceptibility region for bipolar disorder on chromosome 18p11.2: genomic structure and polymorphism screening in manic-depressive patients

Abstract: For several decades, lithium has been the drug of choice in the long-term treatment of manicdepressive illness, but the molecular mechanism(s) mediating its therapeutic effects remain to be determined. The enzyme myo-inositol monophosphatase (IMPase) in the phospholipase C signaling system is inhibited by lithium at therapeutically relevant concentrations, and is a candidate target of lithium's mood-stabilizing action. Two genes encoding human IMPases have so far been isolated, namely IMPA1 on chromosome 8q21.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 29 publications
1
43
1
2
Order By: Relevance
“…The interpretation of the inositol depletion hypothesis has been complicated further by the discovery of a second gene coding for IMPase named IMPA2 (Sjoholt et al, 2000;Yoshikawa et al, 2000). IMPA2 is located on chromosome 18 near a region implicated in linkage studies of manic depressive illness (Berrettini et al, 1994;Rojas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of the inositol depletion hypothesis has been complicated further by the discovery of a second gene coding for IMPase named IMPA2 (Sjoholt et al, 2000;Yoshikawa et al, 2000). IMPA2 is located on chromosome 18 near a region implicated in linkage studies of manic depressive illness (Berrettini et al, 1994;Rojas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It was clear that the four SNPs that we chose initially were too rare and unsuitable to perform LD mapping of the gene. Therefore, we chose three further SNPs: 599 þ 97G4A and 599 þ 99G4A had been reported by Sjoholt et al, 11 and rs3786282 was selected from the public Figure 1). All three SNPs appeared to have minor allele frequencies B30% and we could be confident that they were going to be informative in our populations.…”
Section: Resultsmentioning
confidence: 99%
“…The gene has been mapped to chromosome 18p11.2 10 and its structure has been characterized. 11,12 The gene is a potential biochemical target for the action of lithium. 13 Linkage studies 14,15 have suggested the presence of a susceptibility locus for bipolar disorder on chromosome 18p11.2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations